PALĄ SIEBIE W OGNIU, GDY UMRZE IM KRÓL LUB WÓDZ – I PALĄ RÓWNIEŻ JEGO WIERZCHOWCE. WCZESNOŚREDNIOWIECZNY POCHÓWEK CIAŁOPALNY ZE SZCZĄTKAMI KONIA Z CHODLIKA, POW. OPOLSKI, WOJ. LUBELSKIE - MIECHOWICZ, ŁUKASZ (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The article presents the results of research into an early medieval kurgan in Chodlik, Karczmiska county, where cremated human and horse remains were discovered. The settlement complex in Chodlik (8th-10th c.) forms a vast hillfort of more than 8 ha and the surrounding hamlets. For over a century, it has been subjected to archaeological excavations but it was not until recently that the related cremation burial sites were identified. The first kurgan, examined in 2010, contained buried remains of a human and a horse, most probably buried at a stake together. The other objects found in the upper part of the kurgan included pieces of clay vessels and bronze elements of a horse tack. By means of radiocarbon dating, the burial site’s chronology has been established as the 8th-9th centuries. The text presents comparative analyses with other famous discoveries of the type and considerations of the importance of horses to the early medieval Slavs.